If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+1)=10-2(3-2x)
We move all terms to the left:
4(x+1)-(10-2(3-2x))=0
We add all the numbers together, and all the variables
4(x+1)-(10-2(-2x+3))=0
We multiply parentheses
4x-(10-2(-2x+3))+4=0
We calculate terms in parentheses: -(10-2(-2x+3)), so:We get rid of parentheses
10-2(-2x+3)
determiningTheFunctionDomain -2(-2x+3)+10
We multiply parentheses
4x-6+10
We add all the numbers together, and all the variables
4x+4
Back to the equation:
-(4x+4)
4x-4x-4+4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| -6=(b)/(18) | | 6x+2/4=x+1 | | 2(u+5)-8u=32 | | t+6t=9t-42 | | 3x-12÷4=-6 | | 6r-13/7=r-1 | | 10-5x=10x-35 | | -4x18=x | | -4y+100=28 | | -4=-4y+2(y-8) | | 1/3(18+6x)=2/5(10x+30) | | -n+2=5n-4 | | 2x−4=10−x/3 | | 5+3m=m-3 | | -3x-4+12x-5=-5 | | 5=8+v | | 8x+36=-60 | | -3+u=2 | | 1/4(28a-12)=3/5(5+10a) | | -8x-2=-8x | | 7x-9x+8=-x+8 | | -x+4=10-7x-6(1-x) | | 30x+5=27x-4 | | 2y-6=3y-12 | | 3b-3=45 | | 2x+95x=4 | | 3(x+6)+3=3x+5 | | 8*x=9.6 | | c+5/8=5-9/6 | | y÷2=5 | | 16000y+1500=19300+950 | | 0.25x-3=6x |